2021
DOI: 10.3389/fonc.2021.681441
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Role of Poly (ADP-Ribose) Polymerase Inhibitors as Effective Therapeutic Agents in Renal Cell Carcinoma

Abstract: Renal cell carcinoma (RCC) is the sixth most common cancer in the US. However, no significant changes in management have occurred since the tyrosine kinase era until the recent breakthrough with checkpoint inhibitors. Therefore, the need for more therapeutic options is paramount. Our objective was to determine whether PARP inhibition represents a novel therapeutic option for RCC. We used publicly available COSMIC, GDC Data Portal, and cBioPortal databases to explore mutations in DNA repair genes in RCC tissues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…For example, locally advanced or metastatic genitourinary cancer patients with BRCA1/2 mutations may be treated with poly ADP-ribose polymerase (PARP) inhibitors. Although it has long been known that PARP inhibitors were effective for prostate cancer with pathogenic or likely pathogenic BRCA1/2 mutations [ 46 , 47 ], it was not until recently that evidence started to emerge that PARP inhibitors were also effective in other genitourinary malignancies [ 47 51 ], except in renal cell carcinoma, since no evidence on the presence of BRCA1/2 mutations has been available in the cancer [ 52 ]. Similarly, locally advanced or metastatic cancer patients with germline mutations of MMR genes may be treated with immune checkpoint inhibitors such as PD-l inhibitors, as these cancers generally exhibit high tumor mutational burden and/or high microsatellite instability [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, locally advanced or metastatic genitourinary cancer patients with BRCA1/2 mutations may be treated with poly ADP-ribose polymerase (PARP) inhibitors. Although it has long been known that PARP inhibitors were effective for prostate cancer with pathogenic or likely pathogenic BRCA1/2 mutations [ 46 , 47 ], it was not until recently that evidence started to emerge that PARP inhibitors were also effective in other genitourinary malignancies [ 47 51 ], except in renal cell carcinoma, since no evidence on the presence of BRCA1/2 mutations has been available in the cancer [ 52 ]. Similarly, locally advanced or metastatic cancer patients with germline mutations of MMR genes may be treated with immune checkpoint inhibitors such as PD-l inhibitors, as these cancers generally exhibit high tumor mutational burden and/or high microsatellite instability [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…We sought to determine the correlation between mutations in DDR pathway genes and BLCA patient survival. The list of DDR genes for which we sought to determine mutational status is from [28] and the percentage of mutations found in those genes in BLCA tissues from the TCGA cohort are listed in Table 1. We also report the death rates from BLCA in the TCGA cohort based on mutation rates for each gene, where available.…”
Section: Analysis Of Mutations In Hr Genesmentioning
confidence: 99%
“…We used GDC Data Portal, COSMIC, and cBioPortal to analyze mutation rates in DNA repair genes [28] in BLCA patient tumors from the TCGA. The data revealed that ATM, ERCC2, BRCA2, ATR, and TP53 mutations are highly prevalent in BLCA tissues from the TCGA cohort (Table 1).…”
Section: Blca Patient Tumors From the Tcga Cohort Have Mutations In D...mentioning
confidence: 99%
“…As a PARPi, olaparib reverses drug resistance to sorafenib in liver cancer (90). A total of 27-32% of RCC tissue samples have mutations in HR genes, while PARPi agents (such as niraparib, talazoparib and rucaparib) that target DDR mutations may be effective treatment options for RCC (91). Due to increased PARP1 expression and decreased PARG levels, ccRCC is accompanied by increased levels of poly(ADPribose) (pADPr).…”
Section: Ddr Genes and Precision Treatment Of Renal Cancermentioning
confidence: 99%